Performing Gender Through Women’s Language and Gossip in The Tonight Show Featuring Millie Bobby Brown - Sysca Indriany; Fathur Ramadhan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study examines how women's language features and gossip function as communicative strategies in the performance of gender identity in contemporary media discourse. Drawing on sociolinguistic frameworks proposed by Lakoff, Holmes, Bucholtz and Hall, Eckert and McConnell-Ginet, McAndrew, and Butler's gender performativity theory, this study analyzes Millie Bobby Brown's utterances in The Tonight Show Starring Jimmy Fallon. A qualitative descriptive method was employed, with data collected through purposive sampling of conversational segments containing women's language features and gossip instances. The analysis identified 21 instances of women's language features, including intensifiers, hedges, empty adjectives, politeness forms, and emotional expressions, alongside five instances of gossip serving social bonding, entertainment, and reputation management functions. The findings indicate that these linguistic features do not reflect powerlessness or negative stereotypes; rather, they function as context-dependent performative resources through which the speaker constructs a warm, expressive, and socially engaged gender identity before a mass audience. This study contributes to sociolinguistic research by demonstrating that women's language and gossip are dynamic communicative practices actively employed in the performance of gender in contemporary talk show discourse.